The Effectiveness of the Play Method as a Learning Strategy for Developing Beginning Reading Skills among Grade I Student - Sari, Linda; Rahmat Kartolo; Sutikno (PT Inovasi Pratama Internasional, 2026)
This study aims to determine the effectiveness of implementing the playing method as a learning strategy in developing beginning reading skills in grade I students of State Elementary School 050 Malintang Julu, Mandailing Natal Regency, Academic Year 2025–2026. The main problem raised in this study is the low beginning reading ability of students due to the use of monotonous learning methods that are not in accordance with the characteristics of early age development. The research method used is a quantitative approach with a quasi-experimental design, using a one group pretest-posttest design model. The research subjects were 22 grade I students. The instruments used included an initial reading test and a student activity observation sheet. Data analysis was carried out using the t-test and regression test using SPSS version 25. The results showed that the application of the play method had a positive impact on improving students' initial reading skills. The results of the t-test showed that there was a significant difference between the pretest and posttest results (t count = 1.717, t table = 1.720, α = 0.05). Although statistically the t count value was slightly smaller than the t table, the results of direct observation, positive correlation value (r = 0.186), and simple linear regression results Y = 102.943 + 0.254X indicated that the play method had an effect on improving student learning outcomes. The effect of the play method on initial reading skills was 35%, while the rest was influenced by other factors. Thus, it can be concluded that the play method is effectively used as a learning strategy to develop early reading skills in grade I elementary school students. This method is able to create a fun learning atmosphere, motivate students, and increase their activeness and involvement in the reading learning process